Guide to sustainable development and environmental policy - Mirovit͡skai͡a, N. S. (Natalii͡a Sergeevna); Ascher, William (Duke backfile, 2001)
A compilation of definitions, terms, and critical commentary on aspects of sustainable development and environmental policy, with a strong emphasis on policy tools, policy practices, and systems of international environmental governance.